Modernizing the clinical risk score to more accurately predict survival following resection of colorectal liver metastases - Langan, Russell C.; Carpizo, Darren R. (Translational Gastroenterology and Hepatology; Vol 4 (June 2019): Translational Gastroenterology and Hepatology, 2019)
To date, the National Cancer Institute, NIH estimates 140,250 new colorectal cancer cases for 2018 (1). Out of this population, 20% will present with synchronous metastatic disease and up to 50% will develop metastatic disease. Moreover, in those who develop metastases, the liver is involved 80% of the time. Although historical controls found rare survivors to be noted at 3 years and a median overall survival of 6–12 months in untreated but potentially resectable patients; modern data has found that a multidisciplinary approach incorporating surgical extirpation may allow for up to 55% and 24% actual 5- and 10-year survivors (2,3).